Exploration of Psychological and Cultural Trauma in Selected Nepali Post-Conflict Literature - Pokharel, Badri Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This research paper analyzes psychological and cultural trauma in post-conflict Nepali narratives: Bhaupanthi’s “The Senseless Killing of a Man” and Maya Thakuri’s “The Descending Mountain” by delineating the mental stress and pans of those war victims who were badly affected by the ten-year long Maoist insurgency. Among many war affected people, Rukmana, a terrified mother from both fighting groups, her daughter Muna as well as a government officer who is assigned to hold a district administration office to provide service and security to the people living in the district, but he himself gets sabotaged by his own nephew are in psychological trauma as well as cultural trauma; the trauma of the whole community. This paper tries to answer how they become traumatized and how severely they go through this situation. The main objectives of the paper are to examine the causes of trauma in conflict victims and to delineate what kinds of trauma they suffer from. In doing so, the researcher has used the psychological insight of Caruth, cultural trauma of Alexander and other trauma theorists as theoretical parameter to analyze the primary texts. Here, the researcher examines both stories linking them with the traumatic aspects which would subsequently help one understand personal trauma and the conflict generated consequences in the lives of war-affected people and their socio-political factors associated with contemporary Nepali society.